TESTING OF HIGH TEMPERATURE COATING PHR 1200 EAL - Wiryawan, Andi
PHR 1200 EAL is a slurry coating that said can withstand high temperature up to 1200oC. Until now it is rare to find slurry form coating that could withstand T > 600oC with conventional method application. From that reason, some test is required to prove its high temperatur durability. The evaluation for its high temperature service was based on ASTM D 2485-91 standard. From this test was found that the coating was decomposed to britle and porous ceramic at temperatur above 645oC. Adhesion quality at room temperature was also tested by tape test, scribe test, and bend test. From these tests the coating showed a good quality in adhesion. And from XRD and EDS test, was found that the main ingredients of this coating are silica and aluminium.